Development and validity of the subjective training quality scale - Shell, S. J.; Slattery, K.; Clark, B.; Broatch, J. R.; Halson, S. L.; Coutts, A. J. (European Journal of Sport Science, 2023)
This study aimed to define, develop, and validate a subjective scale of training quality. Two related studies were used to 1) define training quality and 2) develop and validate a subjective scale. Part One: a purposive sample of 15 sub-elite (i.e. national) and elite (i.e. international) swimmers participated in one, 20-30-min semi-structured interview. Thematic analysis of interview responses established three constructs to define training quality. These were the physical, technical, and mental aspects of training. Part Two: development of the Subjective Training Quality (STQ) scale based on the three constructs identified in Part One. 252 sub-elite and elite athletes, across eight sports completed the STQ scale. Cronbach`s alpha (a) assessed internal consistency, histogram plot analysis assessed face validity, and confirmatory factor analysis (CFA) compared physical, technical, and mental constructs with training quality. Root mean square error of approximation (RMSEA) and standardised root mean square residual (SRMR) evaluated CFA quality of fit. Physical, technical, and mental constructs demonstrated a high "acceptable" level of internal consistency (a = 0.85) and excellent face validity. Comparatively, the CFA quality of fit was "excellent" (RMSEA = <0.01 "good", SRMR = 0.00 "perfect"). The STQ scale demonstrated excellent internal consistency and face validity, establishing capacity to monitor training quality. The STQ scale could be used in conjunction with traditional training monitoring tools to provide additional insight into athlete`s training quality. Further investigation is required to determine how the STQ scale may interact with subjective and objective training performance measures, and how it could be incorporated into daily training monitoring.